Preparation of enhanced hydrophobic poly(L-lactide-co-epsilon-caprolactone) films surface and its blood compatibility - Kim, Seung Il; Lim, Jin Ik; Jung, Youngmee; Mun, Cho Hay; Kim, Ji Heung; Kim, Soo Hyun (ELSEVIER, 2013)
Hydrophobicity-enhanced poly(L-lactide- co-epsilon-caprolactone) (PLCL) (50: 50) films were cast by using the solvent-nonsolvent casting method. PLCL (50: 50) was synthesized by the well-known random copolymerization process and confirmed by 1H NMR analysis. The molecular weight of the synthesized PLCL was measured by gel permeation chromatography (GPC). Number-average (Mn), weight-average (Mw) molecular weights and polydispersity (Mw/Mn) were 7 x 10(4), 1.2 x 10(5), and 1.7, respectively. PLCL films were cast in vacuum condition with various nonsolvents and nonsolvent ratios. Tetrahydrofuran (THF) was used as the solvent and three different alcohols were used as the nonsolvent: methanol, ethanol, and isopropyl alcohol (IPA). Surface hydrophobicity was confirmed by water contact angle. The water contact angle was increased from 81 degrees +/- 2. to 107 degrees +/- 2 degrees. Water contact angle was influenced by surface porosity and topography. The prepared film surfaces were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM). The change of crystalline property was characterized by X-ray diffraction (XRD). Platelet adhesion tests on the modified PLCL film surfaces were evaluated by platelet-rich plasma (PRP). The modified film surface exhibited enhanced hydrophobicity and reduced platelet adhesion ratio depending on the surface topography. One of the candidate products proposed as a potential blood compatible material showed a markedly reduced platelet adhesion property. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: SUPERHYDROPHOBIC SURFACE; LOTUS